Do campo de Mandinga à Carta do ABC, do imaterial ao material: o corpo de saberes da Capoeira Angola-ancestral: mediação, performance e memória cultural - Luis Carlos Quintino Cabral Flecha (2021)
The present research proposes a dialogue between Information Science and Capoeira in the investigation in records about the performance in mediation of the information of the body of knowledge of Capoeira Angola-ancestral, considered in this work as a set of living knowledge, carried out by Mestres da Capoeira (Capoeira masters) guided by the presence of the African memory that underlies the struggle of Capoeira in Brazil, based on a decolonial interpretation in the field of Information Science. This research seeks to highlight the episteme that sustains the mediating action of Mestres da Capoeira during the teaching/transmission of the Capoeira fighting technique, and their social protagonism, the act of resisting and re-existing, in the face of the racist, oppressive and mercantile structure that their black bodies historically were and are exposed. The scientific method chosen is qualitative and interpretive in nature, based on primary and secondary documentary sources related to Mestres da Capoeira Angola. The investigation analyzed documental sources include the material of the memorial of the candidacy for the title of Doctor of Notorious Knowledge, to the Mestre da Capoeira Angola in Belo Horizonte, Mr. Edson Moreira da Silva, the Mestre Primo, presented by the postgraduate program in Information Science at UFMG. The investigation in these sources gives centrality to the information of the body-orality linked to the African matrix as a support for materializing the information of ancestral knowledge of Capoeira Angola, making them intelligible in the process of generational communication, in teaching-learning to maintain cultural memory and confrontation to the narrative of modernity and coloniality of power. This work highlights in its analysis the importance of the contexts in which the users of Capoeira information are inserted, proposing Capoeira as well as an informational practice that has its emergence in the relations of black resistance in the society. It is expected that this work will contribute to anti-racist actions within Information Science and to the enhancement of ancestral memories of our African ancestors and the old Mestres da Capoeira de Angola.